THE SECRET OF SUCCESS (CIPEEX, 2022)
THIS WORK WAS PRESENTED DURING THE IX CULTURAL EXHIBITION OF THE DENTISTRY COURSE IN BANNER FORMAT. MANY PEOPLE ASK THEMSELVES, €ŒWHAT IS THE SECRET TO SUCCESS?€ AND SEEK THE ANSWER IN SEVERAL PUBLICATIONS AND BEST SELLERS BY FAMOUS AUTHORS. FOR SOME, THE SECRET IS WAKING UP EARLY, WORKING AND/OR STUDYING HARD, FOR OTHERS, IT'S BEING LUCKY TO BE IN THE RIGHT PLACE AT THE RIGHT TIME. MANY SAY IT'S JUST STUDYING; OTHERS, THAT THEORY ALONE DOES NOT SOLVE AND THAT, IN REALITY, PRACTICE IS WHAT CAN LEAD TO SUCCESS. SOME BELIEVE THAT GOALS CAN ONLY BE ACHIEVED IF PEOPLE ARE BORN IN A GOLDEN CRADLE. SOCIAL NETWORKS ARE TOOLS THAT HAVE CONTRIBUTED TO THE EMERGENCE AND IMPETUS OF PEOPLE OR SITUATIONS THAT HAVE NEVER BEEN SEEN BEFORE. THEY ARE POWERFUL TOOLS, BUT THEY GIVE THE FALSE IMPRESSION THAT SUCCESS CAN BE ACHIEVED EASILY, EFFORTLESSLY, AND AT ANY COST. IT IS INCREASINGLY COMMON FOR PEOPLE TO APPEAR IN UNCONVENTIONAL OR EVEN DEGRADING SITUATIONS, JUST LOOKING FOR LIKES AND SHARES THAT CAN GENERATE A FINANCIAL GAIN. IMAGE AND REPUTATION TAKE A BACK SEAT. BUT THE TRUTH IS THAT THE SECRET TO SUCCESS IS CLOSER THAN YOU THINK. AND TO YOU? WHAT IS THE SECRET OF SUCCESS?
Keywords: culture; dentistry; success